2021
DOI: 10.1136/bjsports-2020-103512
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to improve detection of glucocorticoid doping in sport with new guidance for physicians prescribing for athletes

Abstract: The systemic effect of glucocorticoids (GCs) following injectable routes of administration presents a potential risk to both improving performance and causing harm to health in athletes. This review evaluates the current GC antidoping regulations defined by the World Anti-Doping Agency and presents a novel approach for defining permitted and prohibited use of glucocorticoids in sport based on the pharmacological potential for performance enhancement (PE) and risk of adverse effects on health. Known performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 69 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…Sports dance is an emerging sport with strong technical and artistic qualities; it integrates art, sports, music, and dance, and it is called a model of the combination of “health” and “beauty” [ 1 ]. While the male and female players showed vigorous sports movements, it is also necessary to show the attractive artistic beauty of dance movements.…”
Section: Introductionmentioning
confidence: 99%
“…Sports dance is an emerging sport with strong technical and artistic qualities; it integrates art, sports, music, and dance, and it is called a model of the combination of “health” and “beauty” [ 1 ]. While the male and female players showed vigorous sports movements, it is also necessary to show the attractive artistic beauty of dance movements.…”
Section: Introductionmentioning
confidence: 99%
“…17 19-22 In addition, a recent review of the literature showed a urinary detection period of triamcinolone acetonide ranging from 3 to 8 days after the IA injection, in limited groups of up to eight people. 22 During the Olympic Games in Rio (2016), a register specially created to report on the therapeutic injections performed found that there was significant use of GC injections. 1 Medical doctors, sports and exercise physiologist and sports organisations experts (eg, Fédération Internationale de Football Association and International Cycling Union) have already reported on the excessive use of GC injections prior to competitions, a procedure which is not without consequences to health.…”
Section: Open Accessmentioning
confidence: 99%
“…The novel approach by WADA under way to the 2022 List is the permission or prohibition of glucocorticoids in sport based on the pharmacological influence on performance enhancement and the risk of adverse effects on health. Substance-specific reporting limits are under introduction to the new version of MRPL TD to better distinguish prohibited and permitted use in sport [65].…”
Section: Minimum Required Performance Levels Tdmentioning
confidence: 99%